The Influence of Electronic Service Quality, Transaction Costs and Experience Value on Online Satisfaction and Loyalty of Halodoc Application Users - Asep Rifky Subagja; Febby Fidiyanti; Tri Sutrisno (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
Telemedicine applications are very necessary in efforts to increase the effectiveness of health services to the community. The telemedicine industry has a great opportunity to create market share by properly understanding the important aspects of customer satisfaction. This research aims to identify the factors that most influence customer loyalty which is mediated by customer satisfaction with the halodoc application as a telemedicine application. This type of research is quantitative research using a questionnaire via Google Form as a primary data collection instrument. Secondary data is used in this research as material for developing hypotheses. 200 questionnaire data were analyzed with partial least structural equation modeling (PLS-SEM) using Smart_PLS to validate the model and test hypotheses. The research results show that e-service quality is one of the most influential factors in creating loyalty among halodoc application users, both directly and indirectly, mediated through customer satisfaction. The experience value and transaction cost variables have a positive influence in creating customer satisfaction and loyalty when using the halodoc application. Although this research has several limitations, it is hoped that the research can provide some practical implications for halodoc as a telemedicine company to design application services that produce higher user satisfaction and loyalty.